The Use of Dictionaries Is the Basis of Cognitive Learning - Kamola Saidova (Genius Journals, 2023)
This article talks about dictionaries and their types, classification, and their role for modern man. Different types of dictionaries and principles of their creation are considered. Information is provided about the need to use dictionaries in cognitive education. Examples of exercises and tasks that teach the use of different vocabularies in education are given
Keywords: Dictionary; vocabulary; ideographic dictionary